Impacts on modal choices of new generation freights terminals - B. Jourquin; L. Demilie; Michel Beuthe (European Regional Science Association (ERSA), 1998)
Increasing pollution, congestion of roads and worries about the spatial and environmental impacts of road transports have promoted the idea of transferring part of freight transportation from roads to railways and waterways. Given the limited density of these two modes' networks, this policy implies necessarily the development of inter-modal transports. But their operation on a large scale is meeting several problems : the additional cost of transferring the commodities from one mode or means to another, the size of investments in new technology equipment for terminals, specialized rolling stock and information systems, the involvement of several intermediaries plus the control and management of safety and reliability of the services. In the past, many innovative plans and projects for bundling and transshipping were developed, but many plans were abandoned, and despite a steady growth of inter-modal transports, the results obtained are still limited. At the present time, the most promising projects seem to be the introduction of new shuttle connections on transport links with important flows of transports. However, lower costs and better management of services could probably make attractive the organization of more complex schemes like hub-and-spokes organizations. The paper presents a methodology to model bundling concepts on multi-modal freight networks. It is based on the extensive use of virtual links as they are implemented in the NODUS software developed by GTM . Different configurations of inter-modal networks are modeled which are implemented in a digitized trans-European multi-modal network (rail, road and waterway). Cost functions are associated with every (virtual) link which corresponds to a particular transport operation. A matrix of origins and destinations throughout the European space is generated on the basis of global EUROSTAT statistics by the use of a weighted stochastic procedure. Given this transportation task a minimization of generalized costs can be made which assigns transport flows between paths, modes and means of transport. Hence, successive simulations for different configurations and various parameters' values provide a set of measures of their impacts, which can be used for assessing the interest of concrete inter-modal propositions. The indicators are the market shares, the total operating cost of the transportation task, the total cost of a particular operation, the distances covered, the times of transport, the service frequency required, the energy consumption, etc. This research is part of the EU Commission's TERMINET project which focuses on the potentialities of innovative bundling concepts for transport nodes and terminals.
Keywords: 330